The Influence of Models Portrayed in Beauty Product Television Advertisements Concerning Body Image among Women in Coimbatore City - B, Karthigapooja; Prabha, Dr. R Rama (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Advertising and media play an important role in everyday life and sometimes the message conveyed to women on beauty and body images are skewed. In reality, no one really knows what actual beauty is, so advertisers created an impression by using the elusive models. Portraying unrealistic models in television advertisements resulted in concern about their body image among women. This paper discusses how the beauty product television advertisements portray models with slim body shape and how it influences the women audience. A survey has been conducted in Coimbatore city with a sample of 350 women respondents from different age groups. How to cite this article: Karthigapooja B, Prabha RR. The Influence of Models Portrayed in Beauty Product Television Advertisements Concerning Body Image among Women in Coimbatore City. J Adv Res Jrnl Mass Comm 2019; 6(1): 16-23.